Tuberculosis in migrants in low-incidence countries: epidemiology and intervention entry points - Lönnroth, K.; Mor, Z.; Erkens, C.; Bruchfeld, J.; Nathavitharana, R. R.; van der Werf, M. J.; Lange, C. (The international journal of tuberculosis and lung disease, 2017)
As tuberculosis (TB) rates continue to decline in native populations in most low TB incidence countries, the proportion of TB patients born outside their country of residence ('foreign-born') increases. Some low-incidence countries have experienced a substantial increase in TB rates related to recent increases in the number of asylum seekers and other migrants from TB-endemic countries. However, average TB rates among the foreign-born in low-incidence countries declined moderately in 2009-2015. TB in foreign-born individuals is commonly the result of reactivation of latent infection with Mycobacterium tuberculosis acquired outside the host country. Transmission is generally low in low-incidence countries, and transmission from migrants to the native population is often modest. Variations in levels and trends in TB notifications among the foreign-born are likely explained by differences and fluctuations in the number and profile of migrants, as well as by variations in TB control, health and social policies in the host countries. To optimise TB care and prevention in migrants from endemic to low-incidence countries, we propose a framework for identifying possible TB care and prevention interventions before, during and after migration. Universal access to high-quality care along the entire migration pathway is critical. Screening for active TB and latent tuberculous infection should be tailored to the TB epidemiology, adapted to the needs of specific migrant groups and linked to treatment. Ultimately, the long-term TB elimination goal can be reached only if global health and socio-economic inequalities are dramatically reduced. Low-incidence countries, most of which are among the wealthiest nations, need to contribute through international assistance.